Development of Photo Forensics Algorithm by Detecting Photoshop Manipulation using Error Level Analysis - Teddy Surya Gunawan; Siti Amalina Mohammad Hanafiah; Mira Kartiwi; Nanang Ismail; Nor Farahidah Za'bah; Anis Nurashikin Nordin (Institute of Advanced Engineering and Science, 2017)
Nowadays, image manipulation is common due to the availability of image processing software, such as Adobe Photoshop or GIMP. The original image captured by digital camera or smartphone normally is saved in the JPEG format due to its popularity. JPEG algorithm works on image grids, compressed independently, having size of 8x8 pixels. For unmodified image, all 8x8 grids should have a similar error level. For resaving operation, each block should degrade at approximately the same rate due to the introduction of similar amount of errors across the entire image. For modified image, the altered blocks should have higher error potential compred to the remaining part of the image. The objective of this paper is to develop a photo forensics algorithm which can detect any photo manipulation. The error level analysis (ELA) was further enhanced using vertical and horizontal histograms of ELA image to pinpoint the exact location of modification. Results showed that our proposed algorithm could identify successfully the modified image as well as showing the exact location of modifications.